Global Modern Trends and Scientific Analysis on Green Human Resource Management: A Bibliometric Investigation - Prabhu Prasad Mohapatra; Bandana Nayak; Rabinarayan Patnaik (The Bioscan, 2024)
The organization is currently grappling with increasing competition in the global business arena, facing numerous challenges and striving to sustain its market position through innovation and cost-cutting. The scientific community's interest in management is growing as they seek to establish a niche in this competitive global environment. They are now emphasizing the practicality of green human resource management (GHRM) to guide business units and their human capital towards sustainability. Green HRM aims to foster an organization that encourages employees to take on eco-friendly workplace behaviors while reducing costs. This study aims to synthesize recent global literature and modern trends in green human resource management and carry out a review through scientific analysis and visualization using bibliometric study based on Scopus platform. Bibliometrics is a big data analytic technique used to bring about massive volumes of information. It is a methodology that entails systematic literature reviews and accomplish in depth analysis of academic research with quantitative analysis of scholarly works. VOSveiwer1.6.20 software was used for the study. Research examined 421 documents from the period 2003 to 2024. The study's findings highlight the prominence of green HRM research; identify prolific authors and co-authorship trends, commonly used keywords, and conducting analyses by country and organization, theoretical foundations, and basic statistics. It is observed that China has contributed the highest research papers in green HRM followed by United States and Pakistan. Green industrial relations are still a neglected area in every country. The thorough exploration in this study provides deep insights into the concept of green human resource management, its goals, and its potential benefits for businesses and society.